Gamification: Enhancing Constructivist Skills through Line-Following Robots - Budiman, Ridho Dedy Arief; Surjono, Herman Dwi; Wagiran; Maulana; Hidayat, Edi; Syafruddin, (International Journal of Online and Biomedical Engineering (iJOE), 2025)
This study addresses the challenge of enhancing student engagement and constructivist skills in engineering education by integrating gamification with line-following robots. The problem arises from the need for more interactive and engaging learning experiences in technical disciplines, where traditional methods often fail to actively involve students in the learning process. To tackle this challenge, the study explores how gamification, using game design elements in non-game contexts, can motivate students and create a more dynamic learning environment. The main objective is to investigate the effectiveness of this approach in promoting student engagement, motivation to learn, critical thinking skills, problem solving, and student collaboration, which are all core elements of the constructivist learning theory. The research employs the analysis, design, development, implementation, and evaluation (ADDIE) model as a framework, using a quantitative research design to evaluate both validity and practicality. The study was conducted at the Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Yogyakarta, Indonesia. Data collection involved expert validation from media and gamification specialists, with the average validity scores of 0.90 and 0.89, indicating a highly valid approach. Practicality assessments from educators yielded an average score of 91.85%, while student feedback showed an effectiveness rating of 90.62%. These results highlight the significant potential of combining gamification with robotics to enhance constructivist skills in an engineering education context. Future research should investigate the long-term effects of this integration and explore its applicability across broader educational environments and age groups.